Дослідження завади, що генерується електричним джерелом світлодіодної лампи - Білоцерківець, О. Г.; Воргуль, О. В. (ХНУРЕ, 2020)
LED lamp. The lamp is powered by a switching power supply. The power supply is powered by 220 volts. The power supply is interfering with the radio's ultra-short wavelength range. The lamp and radio are powered by a single 220-volt network. To analyze the operation of the LED lamp, the SSA3021X spectrum analyzer was used. Recommendations regarding the refinement of the lamp circuit diagram are given.
Keywords: LED лампа; SIGLENT SSA3021X; Сигнальний спектр; аналізатор спектру; завади LED лампи